The impact of the commercialization of indigenous forest products on rural livelihoods. A case of Hurungwe North. - Verenga, Temba (Midlands State University, 2017)
The indigenous forest resources formed the basis of rural people’s livelihoods since time immemorial. The importance of these indigenous forest products led to their commercialization in different parts of the world. This study focused on the impact of the commercialization of indigenous forest products on rural livelihoods in Hurungwe North. A number of indigenous forest products have been commercialized. These include a variety of products which are being sold as food, medicines and others. These products include indigenous fruits, vegetables, honey and a variety of products which are being made after processing the forest products. These processed products include household furniture, baskets and mats. Interviews, focus group discussions and questionnaire were used to collect the data in Hurungwe North. The researcher found that, the sale of indigenous forest products such as honey, mats, and wood products is earning the rural people incomes which allow them to access the basic needs. The sale of some of the products such as fruits and vegetables is earning the rural people less income to access the basic needs. In commercialization the indigenous forest products the rural people in Hurungwe North are being challenged by poor transport, unreliable markets and exploitation by the middlemen. Exploitation and sale of the indigenous forest products is leading to problems such as overexploitation of the resources. Rural people should engage in some conservation strategies to avoid the overexploitation of the resources. In order to ensure the profitability of the commercialization of the indigenous forest products the rural people should be taught some basic financial management skills.